Arlo Griffiths, Annette Schmiedchen (eds). The Atharvaveda and its Paippalādaśākhā: Historical and Philological Papers on a Vedic Tradition - Kulikov, Leonid (Acta Orientalia Vilnensia, 2008)
Vilnius University